Changes in the Physiological Parameters of SbPIP1-Transformed Wheat Plants under Salt Stress - G. H. Yu; X. Zhang; H. X. Ma (International Journal of Genomics)
The SbPIP1 gene is a new member of the plasma membrane major intrinsic gene family cloned from the euhalophyte Salicornia bigelovii Torr. In order to understand the physiological responses in plants that are mediated by the SbPIP1 gene, SbPIP1-overexpressing wheat lines and WT plants of the wheat cv. Ningmai 13 were treated with salt stress. Several physiological parameters, such as the proline content, the malondialdehyde (MDA) content, and the content of soluble sugars and proteins, were compared between SbPIP1-transformed lines and WT plants under normal growth or salt stress conditions. The results indicate that overexpression of the SbPIP1 gene can increase the accumulation of the osmolyte proline, decrease the MDA content, and enhance the soluble sugar biosynthesis in the early period but has no influence on the regulation of soluble protein biosynthesis in wheat. The results suggest that SbPIP1 contributes to salt tolerance by facilitating the accumulation of the osmolyte proline, increasing the antioxidant response, and increasing the biosynthesis of soluble sugar in the early period. These results indicate SbPIP1 plays an important role in the salt stress response. Overexpression of SbPIP1 might be used to improve the salt tolerance of important crop plants.